Comparison of Chemical Composition and Energy Property of Torrefied Switchgrass and Corn Stover - Tumuluru, Jaya Shankar (Frontiers in Energy Research, 2015)
In the present study, 6-mm ground corn stover and switchgrass were torrefied in temperatures ranging from 180 to 270°C for 15 to 120-min residence time. Thermogravimetric analyzer was used to do the torrefaction studies. At a temperature of >270°C and a 30-min residence time the mass loss increased to >45%. At 180°C and 120 min there was about 56 and 73% of moisture loss in the corn stover and switchgrass further increasing the temperature to 270°C and 120 min resulted in about 78.8% to 88.18% moisture loss in both the feedstock. Additionally, at these temperatures there was significant decrease in ash and volatile content and increase in the fixed carbon content for both the biomasses tested. The ultimate composition like carbon content increased and hydrogen content decreased with increase in the torrefaction temperature and time. At 270°C and 15 min residence time, the carbon content observed was 54.92 and 53.94% and hydrogen content observed was 2.74 and 3.14%. Nitrogen and sulfur content measured at 270°C and 120 min were 0.98, 0.8, 0.076 and 0.07% for both the corn stover and switchgrass. The H/C and O/C ratio calculated decreased to the lowest values of 0.59 and 0.64, and 0.71 and 0.76 for both biomasses. The van Krevelen diagram drawn for corn stover and switchgrass torrefied at 270°C is closer to coals like Illinois Basis and Powder River Basin. In the present study the maximum higher heating that was observed by corn stover and switchgrass was 21.51 and 21.53 MJ/kg at 270°C and a 120-min residence time. From these results it can be concluded that corn stover and switchgrass, after torrefaction, shows consistent proximate, ultimate, and energy properties.